PENGARUH PENAMBAHAN TEPUNG PORANG TERFERMENTASI DALAM PAKAN LOKALUNTUK MENINGKATKAN PERFOMANCE BABI LOKAL FASE GROWER - Egi Dius Rembo; Wihelmina Loda; Ferdinandus Bai (Jurnal Agriovet, 2024)
This study was conducted with the aim to determine the effect of the addition of fermented porang (Amorphophorus Oncophyllus) tuber flour in local feed to increase the productivity of local pigs in the grower phase. The method used was quantitative research method with experimental research type that included four treatments and repeated three times. The research variables were pig feed consumption, body weight gain, and feed conversion. The results showed that adding fermented porang (Amorphophorus Oncophyllus) tuber flour to local feed had a significant effect (P<0.05) on consumption, weight gain and feed conversion of local pigs in the grower phase. The effect on the performance of local pigs shows that fermented porang (Amorphophorus Oncophyllus) flour can improve and increase the nutritional content of local feed and increase the productivity of local pigs in the grower phase.